HUBUNGAN KELEMBAPAN UDARA DAN CURAH HUJAN DENGAN KEJADIAN DEMAM BERDARAH DENGUE DI PUSKESMAS GUNUNG ANYAR 2010-2016 - Ratna Maya Paramita; J. Mukono (Universitas Airlangga, 2017)
Dengue hemorrhagic fever is caused by dengue virus. The number of cases reported annually to World Health Organization ranged from 0,4 to1,3 million in the decade 1996–2005. The outbreak is annually happen on some provinces in Indonesia. The outbreak at 1998 and 2004 were the most cases in number. Surabaya city was an endemic area. It had suffered 640 people with 13 people were dead in 2015, which case fatality rate was 2,03%. This study aims to analyze a correlation of humidity and r ainfall with the incidence of d engue hemorrhagic fever at Gunung Anyar Primary Health Care, 2010–2016. The method of this research was time trend ecological study with the unit of analysis was per month during seven years. The results were showed that humidity correlated with dengue hemorrhagic fever (p = 0.002 and r = + 0.351). So did the r ainfall (p = 0.042 and r = + 0.230). This research was concluded that humidity and rainfall correlated significantly with the incidence of dengue hemorrhagic fever. Sign of positive meant when humidity and rainfall increased, the incidence of dengue hemorrhagic fever increased too. Climate condition at Gunung Anyar district supports to make the incidence of dengue hemorrhagic fever happen. Because of that, people should improve their attention when peak seasons are coming, like doing mosquito breeding place elimination, keeping fish of mosquito larva predators, and using repellent among daily activities.